The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00737-018-0849-7
|View full text |Cite|
|
Sign up to set email alerts
|

PTSD and gender: could gender differences in war trauma types, symptom clusters and risk factors predict gender differences in PTSD prevalence?

Abstract: The female-male ratio in the prevalence of post-traumatic stress disorder (PTSD) is approximately 2:1. Gender differences in experienced trauma types, PTSD symptom clusters, and PTSD risk factors are unclear. We aimed to address this gap using a cross-sectional design. A sample of 991 civilians (522 women, 469 men) from South Lebanon was randomly selected in 2007, after the 2006 war. Trauma types were grouped into disaster and accident, loss, chronic disease, non-malignant disease, and violence. PTSD symptom c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
3
18
2
Order By: Relevance
“…This effect could translate into hyperarousal in women under conditions of norepinephrine hypersecretion that occur in PTSD (Bangasser et al, 2013). However, it is noteworthy that the incidence of various types of trauma is generally also disproportionate between males and females, hence further investigations for confounding factors are necessary (Farhood et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This effect could translate into hyperarousal in women under conditions of norepinephrine hypersecretion that occur in PTSD (Bangasser et al, 2013). However, it is noteworthy that the incidence of various types of trauma is generally also disproportionate between males and females, hence further investigations for confounding factors are necessary (Farhood et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the prevalence of PTSD has been shown to be substantially higher in women. 16 This has been re-substantiated in the setting of the COVID-19 outbreak in Wuhan, China, where women scored significantly higher on the PCL-5 (DSM-5 self-report measure for PTSD) than men, including higher rates of re-experiencing and negative alterations in cognition or mood. 17 Early recognition and effective treatment can ameliorate the burden of PTSD on both the individual and society, particularly for women who have been shown to have a modest advantage with regard to treatment response.…”
Section: Implications For Covid-19 Managementmentioning
confidence: 94%
“…For instance, there is evidence to suggest that among those who have experienced a traumatic event, women were at greater risk for experiencing flashbacks, hypervigilance, and intense emotional reactions to trauma reminders than men, whereas men were at greater risk for feelings of detachment than women (Tekin et al, 2016). Another study showed gender differences in items within specific symptom clusters, such that women were more likely to report internal avoidance behaviors whereas men reported more external avoidance behaviors, and women were more likely to report increased startle responses whereas men reported increased irritability and anger outbursts (Farhood et al, 2018). However, these studies did not account for the type of trauma experienced.…”
Section: Introductionmentioning
confidence: 99%